Neue palaearktische und afrikanische Coccinellidae (Coleoptera). - Fürsch, Helmut (Contributions to Entomology = Beiträge zur Entomologie, 1960)
Some Coccinellid species named in litteris by Weise and Korschefsky but not published are described here (Scymnus jormosanus, togoensis, Novius nigerrimus, Ortalia prosternalis), or referred to the identity with species already described by other authors. Two more species collected by Hans Knorr/Stuttgart during Prof. Eisentraut's expedition to Camerun mountain (Afissa impatiens, Thea machatschkei) are described as new.Nomenclatural Actsimpatiens Fürsch, 1960 (Afissa), spec. n.nigerrimus Fürsch, 1960 (Novius), spec. n.prosternalis Fürsch, 1960 (Ortalia), spec. n.formosanus Fürsch, 1960 (Scymnus (s. str.)), spec. n.togoensis Fürsch, 1960 (Scymnus (s. str.)), spec. n.machatschkei Fürsch, 1960 (Thea), spec. n.